Effects on jump shooting accuracy when using unstable surfaces for functional balance training of youth basketball players - Ibrahim, N. A.; Zajac, T.; Lupu, G.; Saad, M.; Drozd, M.; Shani, H.; Larion, A.; Essa, W.; Saleh, T.; Hashim, M.; Hamza, A. S.; Alhasany, M. H. (Journal of Human Kinetics, 2025)
This study examined the effects of a 10-week functional balance training program using unstable surfaces on dynamic postural control, lower-limb power, and technical shooting performance in adolescent male basketball players. Twenty-one participants were assigned to an experimental group (n = 11; age 16.14 ± 1.13 years) or a control group (n = 10; age 16.89 ± 1.34 years). Both groups trained three times per week over the intervention period. The experimental group completed additional neuromuscular exercises on unstable surfaces, while the control group performed traditional resistance-based routines. Pre- and post-intervention assessments included the Y-Balance Test (YBT), vertical jump height, and jump shooting accuracy (JSA). Statistically significant improvements in dynamic balance (p < 0.001, d = 1.84) and shooting efficiency (p < 0.001, d = 1.78) were observed in the experimental group. The control group also improved significantly in balance (p = 0.021, d = 0.87) and shooting accuracy (p = 0.014, d = 0.95), but to a lesser extent. Between-group comparisons demonstrated significant advantages for the experimental group in both the YBT (p = 0.007, d = 1.00) and JSA (p = 0.004, d = 1.07). No significant improvements were found in vertical jump performance in either group (p > 0.05). These findings suggest that incorporating functional balance training into basketball conditioning programs may enhance postural control and technical shooting execution, with a notable effect size, particularly in dynamic balance. The improvements in Y-Balance scores indicate enhanced sensorimotor control, although further research is needed to clarify the underlying neuromechanical mechanisms.